School library management - Harvey, Carl A. II; Church, Audrey P. (Santa Barbara, California Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2022)
"Highlighting activities and discussion questions that will pique student interest and facilitate instruction, the 8th edition of this well-known school library text gathers management articles into a ready-to-use volume that showcases current best practices"--Provided by publisher.
Includes bibliographical references and index.
Keywords: School libraries -- United States -- Administration